Neighborhood Social Vulnerability and Racial Disparities in Schizophrenia Spectrum Disorder Prevalence - Anglin, Deidre M; Olfson, Mark; van der Ven, Els; Oh, Hans; Lewis-Fernández, Roberto; DeVylder, Jordan; Oluwoye, Oladunni; Dixon, Lisa; Stroup, T Scott; Guyer, Heidi; Bareis, Natalie (The American journal of psychiatry, 2025)
The study aim was to identify ethnoracial disparities in the prevalence of schizophrenia spectrum disorders (SSDs) and positive psychotic symptoms in the United States and examine the role of social neighborhood inequities. Participants in the Mental and Substance Use Disorders Prevalence Study, a national household sample of nonelderly adults (N=4,764), were assessed by clinicians with the Structured Clinical Interview for DSM-5 (SCID-5) for SSDs (past year and lifetime), including schizophrenia, schizoaffective disorder, and schizophreniform disorder, and for psychotic symptoms. Weighted logistic regression models estimated ethnoracial differences in the prevalence of SSDs and psychotic symptoms in unadjusted models, age- and sex-adjusted models, and models further adjusted for a neighborhood Social Vulnerability Metric (SVM) score, a composite index of five social determinants of health domains. Compared to non-Hispanic White individuals, non-Hispanic Black individuals had a significantly higher prevalence of SSDs (4.1% vs. 1.2%; adjusted odds ratio=3.49, 95% CI=1.37, 8.91) and psychotic symptoms (9.3% vs. 4.9%; adjusted odds ratio=2.04, 95% CI=1.15, 3.63), and non-Hispanic multiracial individuals had a significantly higher prevalence of SSDs (5.6%; adjusted odds ratio=4.59, 95% CI=1.53, 13.76). Further adjustment for SVM score lowered the Black-White group difference for SSDs (adjusted odds ratio=2.49, 95% CI=0.63, 9.90) and psychotic symptoms (adjusted odds ratio=1.69, 95% CI=0.83, 3.44), and the associations were no longer statistically significant. The difference in SSDs between the non-Hispanic multiracial and White groups was attenuated after SVM score adjustment (adjusted odds ratio=3.95, 95% CI=1.30, 12.00) but remained significant. This national U.S. household study found ethnoracial differences in the prevalence of clinician-assessed SCID-based schizophrenia spectrum disorders and positive psychotic symptoms. The higher prevalence among minoritized groups, particularly Black individuals, was connected to social inequities and community-level vulnerabilities embedded in neighborhoods and associated with structural racism.